Enhanced Photocatalytic Property of Cu Doped Sodium Niobate. (20th October 2015) - Xu, Jianbin; Zhang, Feng; Sun, Bingyang; Du, Yingge; Li, Guoqiang; Zhang, Weifeng
Abstract : We investigate the photocatalytic activity of Cu doped NaNbO3 powder sample prepared by the modified polymer complex method. The photocatalytic activity of hydrogen evolution from methanol aqueous solution was improved by Cu 2.6 at% doping. The photocatalytic degradation of rhodamine B (RhB) under visible light irradiation was enhanced in comparison with pristine NaNbO3 . Cu introduction improved the adsorption property of NaNbO3, judging from the Fourier transform infrared spectra. Moreover, the ultraviolet light excitation in Cu doped sample would accelerate the mineralized process.